Hospital admission for acute pancreatitis in the Irish population, 1997-2004: could the increase be due to an increase in alcohol-related pancreatitis? - CONLON, KEVIN CHRISTOPHER; ALLWRIGHT, SHANE PATRICIA ANN; O'FARRELL, ANNE; TOOMEY, DESMOND PAUL (Oxford University Press, 2007)
OBJECTIVE: To investigate trends in the incidence of acute pancreatitis by examining emergency admissions to acute public hospitals over an 8-year period; to compare trends for alcohol-related pancreatitis admissions with biliary tract-related admissions and to profile the patients admitted with an acute pancreatitis diagnosis. METHODS: All in-patient emergency admissions for which an acute pancreatitis diagnosis (ICD-9-CM Code 577.0) was recorded as principal diagnosis were identified for years 1997-2004 inclusive. Alcohol-related acute pancreatitis admissions (i.e. had alcohol misuse recorded as co-morbidity) were identified using ICD-9-CM-codes 303 and 305. Biliary tract disease-related admissions (i.e. had biliary tract disease recorded as co-morbidity) were identified using ICD-9-CM codes 574.0-576.0 inclusive. Pearson's chi2-test was used to compare proportions in groups of categorical data and chi2-tests for trend were used to identify linear trends. RESULTS: There were 6291 emergency admissions with a principal diagnosis of acute pancreatitis during the 8 year study period, with 622 admissions in 1997 compared to 959 admissions in 2004, an increase of 54.1%. Age standardized rates rose significantly from 17.5 per 100,000 population in 1997 to 23.6 per 100,000 in 2004, (P<0.01 for linear trend). There were 1205 admissions with alcohol misuse recorded as a co-morbidity increasing from 13.9% (87/622) of acute pancreatitis admissions in 1997 to 23.2% (223/959) in 2004. This increase was significantly greater than the increase observed for biliary tract disease-related admissions, 19.6% (122/622) in 1997 to 23.5% (225/959) in 2004. Rates for total acute pancreatitis admissions were highest in those aged 70 years and over; the majority (3563, 56.6%) of the admissions were male with a mean age of 51.1 years (SD 19.9); the mean age for male admissions was significantly younger than for female admissions (49.1 versus 53.6 years, P<0.001). However, for alcohol-related admissions, rates were highest in those aged 30-49 years and patients admitted with alcohol misuse recorded were significantly younger than those who did not have alcohol misuse recorded (42.0 versus 53.2 years, P<0.001). Median length of stay was 7 days. CONCLUSIONS: Hospital admissions for acute pancreatitis rose from 17.5 per 100,000 population in 1997 to 23.6 per 100,000 in 2004. The proportion of admissions that had alcohol misuse recorded as a co-morbidity rose more markedly than those with biliary tract disease and the rise was more pronounced in younger age groups. The increasing trend in alcohol-related acute pancreatitis parallels the rise in per capita alcohol consumption. Given the continuing rise in binge drinking, particularly among young people, this is a cause for concern.
PUBLISHED
Keywords: Public Health; acute pancreatitis